Manajemen Penerimaan Siswa Baru Berbasis Online di Lembaga Pendidikan Islam - Cindy, Cindy; Muhabibudin, Nur; Ramdhani, Ratna Dwi; Jarya, Haenul; Akmaliah, Qatrunnada Jinan; Dewi, Nur Sartika (JURNAL ILMU PENDIDIKAN & SOSIAL (SINOVA), 2025)
This research aims to explore and analyze the implementation of online-based new student admissions management in Islamic educational institutions. The problems identified include challenges in the new student admissions process, the effectiveness of the online system, and stakeholder perceptions of the use of technology in admissions management. The research method used is a case study with a qualitative approach, involving in-depth interviews with admissions managers, administrative staff, and prospective students. The research results show that the online system has provided efficiency in the admission process, but still faces several technical obstacles and resistance from several stakeholders. In addition, it was found that technology-related training and effective communication could increase acceptance of the new system. In conclusion, online-based new student admissions management offers the potential to increase efficiency and accessibility, but requires appropriate adjustments and strong support from all relevant parties